Curricular Integration: Articulation Between Educational Institutions, Local Agents and Young Citizens of La Argentina de Pocora, Limón, Costa Rica - Vargas-Vargas, Bryan Roberto (Universidad del Rosario, 2021)
This article illustrates the pedagogical experience of curricular integration in the articulation with educational institutions, local agents, and young citizens of the rural community of La Argentina, Pocora. It is discussed several aspects such as the school-community relationship, curricular integration, the construction of a common problem, and the epistemological position. This document will show the stages carried out in the pedagogical project, from the consultative stages with the community, to its implementation. It concludes on the importance of teaching-learning anchored to the community to think within the conditions, opportunities, or difficulties of its own as a transforming.